An estimate of extracellular vesicle secretion rates of human blood cells. Issue 6 (2nd June 2022) - Auber, Martin; Svenningsen, Per
Abstract: Extracellular vesicles (EVs) have been implicated in the intercellular transfer of RNA and proteins through cellular secretion into the extracellular space. In blood plasma, circulating EVs are mainly derived from blood cells; however, factors that control plasma EV abundance are largely unknown. Here, we estimate the EV secretion rates for blood cell types using reported values for cell‐specific plasma EV abundances and their parental cell's ubiquity in healthy humans. While we found that plasma contains on average ∼2 plasma EVs/cell, the cell‐specific EV‐to‐cell ratio spanned four orders of magnitude from 0.13 ± 0.1 erythrocyte‐derived EVs/erythrocyte to (1.9 ± 1.3) × 10 3 monocyte‐derived EVs/monocyte. The steady‐state plasma EV level was maintained by an estimated plasma EV secretion rate of (1.5 ± 0.4) ×  10 12 EVs/min. The cell‐specific secretion rate estimates were highest for monocytes (45 ± 21 EVs/cell/min) and lowest for erythrocytes ((3.2 ± 3.0) ×  10 −3 EVs/cell/min). The estimated basal cell‐specific EV secretion rates were not significantly correlated to the cell's lifespan or size; however, we observed a highly significant correlation to cellular mitochondrial enzyme activities. Together, our analysis indicates that cell‐specific mitochondrial metabolism, for example, via reactive oxygen species, affects plasma EV abundance through increased secretion rates, and the results provide a resource for understanding EV function in human health and disease.